2003
DOI: 10.2307/1593683
|View full text |Cite
|
Sign up to set email alerts
|

Writing Issues in College Students with Learning Disabilities: A Synthesis of the Literature from 1990 to 2000

Abstract: This article provides a synthesis of the literature published from 1990 to 2000 on college students with learning disabilities and writing difficulties (LD/WD). Thirty-eight articles met the criteria for describing writing difficulties in this cohort of students. Upon reviewing the articles, four major topics emerged: (a) assistive technology for college students with LD/WD; (b) effectiveness of assistive technology for college students with LD/WD; (c) characteristics and error patterns in the writings of coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…This is supported by the results of a metanalysis carried out on children, which found little validity in the use of IQ in identifying students with dyslexia (Stuebing et al 2002). Variation in the specific tests used to diagnose dyslexia may also lead to a blurring of the boundaries of diagnosis between students (Li and Hamel 2000;Rorebraugh 2000). This would not explain why more students are coming forward for testing and, in any case, most of the students display other features of SpLD such as deficient organisational skills and problems with short term memory.…”
Section: Percentage (%)mentioning
confidence: 97%
See 1 more Smart Citation
“…This is supported by the results of a metanalysis carried out on children, which found little validity in the use of IQ in identifying students with dyslexia (Stuebing et al 2002). Variation in the specific tests used to diagnose dyslexia may also lead to a blurring of the boundaries of diagnosis between students (Li and Hamel 2000;Rorebraugh 2000). This would not explain why more students are coming forward for testing and, in any case, most of the students display other features of SpLD such as deficient organisational skills and problems with short term memory.…”
Section: Percentage (%)mentioning
confidence: 97%
“…Engagement with student services, determination and motivation have all been shown to increase success (Heiman and Parecel 2003;Raskind et al 1999;Reiff et al 1992). Although the success of specific educational interventions has been hampered by a lack of research in this area (Li and Hamel 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Of course, different investigators use different ICTs; in several instances these are multipurpose products designed especially for the study. Indeed, Li and Hamel (2003), who undertook a systematic review of ICTs and students with LDs for the period 1990 to 2000, found only four empirical studies of effectiveness. Our own literature review, conducted in 2012, also revealed a shocking paucity of empirical studies and no conclusive findings.…”
Section: Recommendationsmentioning
confidence: 99%
“…As Lindstrom (2007) comments, there are very few studies on college student writers with learning disabilities. As an illustrative example, Lindstrom reports the systematic review of Li and Hamil (2003) who found 38 empirical studies on the effectiveness of assistive technology for students with learning disabilities between 1990 and 2000, only four of which included postsecondary students.…”
Section: Literature Searchmentioning
confidence: 99%